Kje so meje lobiranja - Ribičič, Ciril (Podjetje in delo, 2014)
The first part of the article deals with the state of corruption in Slovenia and points to the need to strengthen the Commission for the Prevention of Corruption as well as to the need to reinforce the legislation regulating its position and jurisdiction. It also emphasizes the need for effective protection of human rights of those affected by the Commission and for a greater oversight over its functioning. In the second part, the article deals with corruptive lobbying in three fields: in the field of chimney cleaning activity both the influencing of concessionaires on political decision-making, plagued by corruption risks, and the positive activities of civil society movements - founded by unsatisfied users of chimney cleaning services - are presented; the development of rules and restrictions in the field of lobbying in the EU Parliament, developed in response to corruption affairs and scandals are also presented. Finally, corruption risks in the formation and working of one Slovenian political party are analysed. The first part is intended to give an overall picture of corruption risks in Slovenia, the second part of the article deals with concrete forms of corruptive lobbying.
Keywords: interesne skupine; korupcija; lobiranje; pravna ureditev; preprečevanje